Assessing Rural Entrepreneurial Intentions of Adults in Mabaalstad in the North West Province - Maphela, Bulelwa; Godana, Nkululeko (Journal of Ecohumanism, 2025)
Rural areas are characterised by poverty and unemployment. Many people who live in rural areas are ensnared in a cycle of poverty. The unemployment rate in Mabaalstad village, which is part of Ward 25 of the Moses Kotane Local Municipality in the North West province, is very high. The Integrated Development Plan (IDP) 2017/2022 of the municipality reveals an unemployment rate of 51%. The high unemployment rate and great poverty are compounded by the low education levels, which implies that skills development is necessary, and that job creation needs urgent attention. Among the interventions that can help are training and skills development for small-medium enterprises and fostering of a culture of entrepreneurship. Entrepreneurship capacity can be built in Mabaalstad through a skills development programme. An entrepreneurship-intentions assessment can help the municipality to identify the skills that already exist compared to what is required in terms of the opportunities that have been identified by the IDP. Thus, the main objective of this study was to assess the entrepreneurial intentions of the adults in Mabaalstad in the North West province of South Africa. The study uses the theory of planned behaviour (TPB) and Shapero and Sokol’s model of entrepreneurial event (SEE) to explore the relationships of the variables within the models with entrepreneurial intention. The findings confirmed that the participants in the study, regardless of the challenging circumstances in Mabaalstad, do have an intention to start their business ventures.